Is the UK National Debt Sustainable? - Clark, Ella; Vasilev, Aleksandar (Journal of Mathematical Economics and Finance, 2024)
National debt sustainability is a very topical discussion, as it continues to increase each year for many countries. This analysis is on the UK, one of the most advanced economies, using macroeconomic theories to study the national debt and its effects. This study was split into different research aims, focusing on the variables used throughout this study. This study used Vector Auto Regression, VAR, models to produce Impulse Response Functions, IRF’. To show the level of the impact, as well as the statistical significance of the effects. The results of this study were clear and showed that the use of fiscal policy was effective and when aggregate tax revenue increased, the national debt decreased. It also found that Annually Managed Expenses, AME’s, did not have a significant impact on the national debt, making these costs justified. Along with using different tax revenue collection methods which showed support to the economy in the long run. This study offered a different insight into debt sustainability for the UK and was concluded that the UK national debt was sustainable.